Website government program: behavior intention accounting student based on the UTAUT model - Diyah Probowulan; Ardiyanto (Proceeding International Conference on Accounting and Finance, 2023)
The purpose of this paper is to analyze the factors that influence behavioral intentions on the use of learning website programs in undergraduate students and future expectations about the development of learning in the field of accounting, which is in line with the information system. The approach is carried out using the UTAUT model. A total of 411 accounting undergraduate students were invited to participate, but only 309 responded. Participants looked through the big data website for the Indonesian government’s learning program. The findings showed higher performance expectations, effort expectations, social influence, and facility conditions for the use of the website would increase behavioral intentions. The study also showed that the strength of the link between social influences on interest behavior and the student’s gender was related to the strength of the relationship between performance expectations and business expectations. This study expands the behavioral development of accounting knowledge through the use of educational technology. As for policymakers, the study shows that they are considering technology-based learning models, building a science and technology mindset, and motivating students to better master big data analytics. This study was conducted on students who used the Indonesian government program website as a learning process and focused on accounting, student work expectations, and their assessment of the academic experience. This study can assist the college in developing policies related to student retention and success. These studies could help HEI come up with policies and programs to help accounting students make the move from college to the workplace.